Enhancing Corrosion Resistance and Tribomechanical Characteristics of Powder Coatings via the Integration of Functionalized HF-Free MXene Reinforcements - Nazarlou, Ziba; Peighambardoust, Naeimeh Sadat; Motlagh, Peyman Lahe; Aydemir, Umut (Wiley, 2025)
MXene, a new generation of 2D materials, is gaining attention for anti-corrosion applications due to its large surface area, electrical conductivity, and self-healing properties. Its low shear strength and self-lubricating properties enhance wear resistance. Herein, silane functionalized HF-Free MXene nanosheets MS-f_Ti3C2 and MS-f_Ti3C2@Zn synthesized through the molten salt method are integrated into the environmentally sustainable powder coating. The electrochemical tests indicate that a powder coating containing a well-dispersed 1.5 wt.% f_Ti3C2@Zn nanosheets exhibit the highest polarization resistance (1.1 x 106 ohm cm2), lowest Icorr (2.15 x 10-8 A cm-2) and superior anti-corrosion performance after 42 days of immersion in 3.5 wt.% NaCl. The polarization resistance (Rp) and corrosion current (Icorr) of the untreated coating are measured to be 1.6 x 103 ohm cm2 and 1.6 x 10-5A cm-2, respectively. In addition, the incorporation of MXene material reduces crack development and spalling, and enhances wear resistance during the friction process. The loading of 1.5 wt.% f_Ti3C2@Zn reduces the coefficient of friction (COF) and improves wear rate by 45% and 51%, respectively Analysis of composites via nanoindentation reveals such enhanced mechanical properties. This study presents an effective and sustainable approach to improve the mechanical, tribological, and long-term corrosion protection of organic coating, thereby exhibiting great potential for using HF-Free MXene as a multipurpose additive. Incorporating amino silane-functionalized, HF-free MXene nanosheets into eco-friendly powder coatings significantly enhances corrosion resistance and tribomechanical properties. The addition of just 1.5 wt.% of these nanosheets improves mechanical strength, reduces friction, and provides superior long-term corrosion protection. This sustainable approach offers a high-performance coating solution suitable for a wide range of applications. image
Keywords: anticorrosion; molten salt; MXene; nanoindentation; tribology